Non-Finance Managers’ Perspectives on the Role of Management Accountants: The Case of Gold Mining Companies in Ghana. - Tettevi, R. (University of Ghana, 2019)
The gold mining industry is a price taker, a predicament that makes cost control and management the most important consideration to maximise profit. Despite the growing concern for employing management accountants to utilize modern management accounting techniques to control cost, mining companies continue to adopt traditional methods of cost control. The study, therefore, seeks to investigate the perceptions of non-finance managers on the role of management accountants and the extent of support and emphasis that these managers place on management accountants. This study is an interpretative qualitative research which adopts a case study approach. The instruments used were interviews and publicly available documents. The data is analyzed using thematic analysis. The study finds that non-finance managers perceive the role of management accountants to include; bookkeeping, budget preparation, cost awareness and management and adoption of modern costing techniques. However, management accountants do not play the role of cost awareness and management effectively. Also, the adoption of modern costing methods is low in gold mining companies . The study recommends that management of gold mining companies should sponsor management accountants in the corporation to learn modern accounting techniques and encourage the use of these techniques to control cost. Also, management accountants should create cost culture among the operational staff to be cost conscious and play active role in controlling cost in the organisation. The study also recommends future research that focus on management accountants’ perspectives on the role of modern management techniques in gold mining companies.
MSc.
Keywords: Management Accountants; Gold Mining; Ghana